Riverine Identity: Investigating Whitewater Paddlers' Connectedness to Nature - Sam Beichler (UNC Test Journal, 2024)
The goal of this study was to determine if a whitewater paddler’s connectedness to nature was impacted by their skill level. This study also sought to identify the emotional mechanisms associated with the relationship between skill level, days spent paddling, or years spent paddling and their connection to nature. Participants (n=389) answered demographic questions and responded to Susan Clayton’s Environmental Identity Scale and three qualitative questions that focused on the emotional trends that paddlers experience. Beyond skill level, the demographics of years spent paddling and days spent paddling collected. Results showed that skill level did not impact connectedness to nature. The other variables were then analyzed to determine if they impacted connectedness to nature. Days spent paddling per year was found to positively impact connectedness to nature, as people who paddled more than 50 days a year scored higher on the Environmental Identity Scale. This suggests that paddlers who spent more time outside are more connected to nature. Feelings of well-being, flow state, and an affinity for nature were common emotional mechanisms reported by people who paddled more than 50 days a year. They were less likely to report experiencing adrenaline and thrill, increased anxiety, or engaging in activities other than paddling. This study further adds to the research of ecopsychology by supporting the premise that spending more time outside positively impacts someone’s connectedness to nature. One unique contribution is the exploration of emotional mechanisms that are associated with paddlers’ experiences, which can potentially help develop programs that connect more people to nature.